Management of Cracked tooth syndrome: A case Report - Shikdera, AHM Zakir Hossain; Quader, SM Abdul; Chowdhury, Shirin Sultana; Begum, Ferdousi; Hasan, Md Nazmul (Update Dental College Journal, 2014)
Cracked tooth is a distinct type of longitudinal tooth fracture which occurs very commonly and its diagnosis can be challenging. This type of fracture tends to grow and change over time. Clinical diagnosis is difficult because the signs and symptoms are variable or nonspecific and may even resemble post-treatment disease following root canal treatment or periodontal disease. This variety and unpredictability make the cracked tooth a challenging diagnostic entity. In this paper we present a case of cracked tooth and emphasise on the timely proper diagnosis and management. DOI: http://dx.doi.org/10.3329/updcj.v4i1.21176 Update Dent. Coll. j: 2014; 4 (1): 53-58